Words or deeds - what matters? Experience of recentralization in Russian security agencies - Alexander Libman (Frankfurt School of Finance & Management, 2010)
The paper discusses the relative importance of the 'real' political actions versus the changes of symbolic nature in the bargaining over devolution, studying the case of personnel decentralization in security agencies in Russia in 2000-2007. While in the 1990s under Boris Yeltsin regional branches of federal ministries in Russia were mostly captured by regional governors, allowing them to pass acts directly contradicting federal law, in 2000s the administration of Vladimir Putin gradually replaced the heads of regional branches by new bureaucrats, supposedly without any connections to the region. The results differ for different security agencies; however, the paper finds, surprisingly, that in several cases the appointment decisions were robustly influenced rather by symbolic gestures made by regional governments in the earlier bargaining process than by the actual devolution policies of the regions.
Keywords: D78; H77; P26; 330; Devolution; bargaining; transition economies; Zentralstaat; Regionalverwaltung; Verhandlungen; Public Choice; Russland